UPAYA - UPAYA YANG DILAKUKAN STASIUN RADIO DALAM MENJARING PEMASANG IKLAN KEPADA PENDENGAR (Suatu Studi pada PT. Radio Chakra Bhuwana Malang) - Antonius Doi Dori (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
Abstract: Malang city's famous progressive in providing information, not least with the city - the other big cities in Indonesia. Currently the city of Malang as fertile ground for business information in the packaging media, both print and electronic media, one of the advanced electronic media and still survive a radio. Radio broadcasting is a mass communication media components are used as conveying of information. Which can reach almost all city residents malang, any time, any place, and involve everyone (even illiterate) as well as anywhere. The technology used is very possible to overcome geographic barriers radio, weather and time.Moreover, with the development of satellite technology, radio is the cheapest electronic media, both the radio transmitter and receiver can be done while doing other things.Along with the development of this type of radio is radio the government, semi- government and private radio a much-loved community, especially among the middle down private radio with young segmentation not only convey just information but also entertainment, humor private radio as a means of entertainment evolved eventually play a significant role significant as the mass media.The method used is descriptive qualitative, aiming to gather information and facts - facts and phenomena investigated. It can be concluded that the Chakra Bhuwana FM radio listeners has increased the satisfaction of the needs - the needs and personal desires in a hearing broadcast on radio Bhuwana chakra, because in previous studies advertisers levels were obtained only at the intermediate level and above, and in this study the level of installer listeners classified ads to increase, as advertisers embrace the middle and upper-and middle down. Keywords: efforts - the efforts of radio stations in attracting advertisers to the audience Abstrak :Radio siaran merupakan komponen media komunikasi massa digunakan sebagai sarana penyampai informasi.Yang dapat dijangkau hampir seluruh warga masyarakat kota malang, setiap waktu, setiap tempat, dan melibatkan siapa saja (bahkan orang buta huruf) serta di mana saja. Teknologi yang digunakan pun sangat memungkinkan radio untuk mengatasi hambatan geografis, cuaca maupun waktu. Seiring perkembangan radio dari jenis radio yaitu pemerintahan, semi pemerintah dan swasta Radio yang banyak digemari masyarakat khususnya di kalangan menengah kebawah yaitu radio swasta dengan segmentasi muda yang bukan hanya menyampaikan sekedar informasi tapi juga hiburan, humor radio swasta sebagai sarana hiburan akhirnya berkembang memainkan peran cukup signifikan sebagai media massa. Metode yang digunakan adalah deskriptif kualitatif, bertujuan untuk mengumpulkan informasi,dan fakta-fakta serta fenomena yang diselidiki. Dengan demikian dapat disimpulkan bahwa pendengar Radio Chakra Bhwana Fm mengalami peningkatan kepuasan terhadap kebutuhan-kebutuhan dan keinginan pribadi dalam mendengar siaran di radio chakra bhuwana, karena pada penelitian sebelumnya tingkat pemasang iklan yang diperoleh hanya berada pada level menengah keatas, dan pada penelitian ini tingkat pemasang iklan kepada pendengar dikategorikan meningkat, karena merangkul pemasang iklan menengah keatas dan menengah kebawah. Kata kunci : upaya - upaya yang dilakukan stasiun radio dalam menjaringpemasang iklan kepada pendengar